ABC Based Design of PID Controller for Two Area Load Frequency Control with Nonlinearities - M. Elsisi; M. Soliman; M. A. S. Aboelela; W. Mansour (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper presents an application of the Artificial Bee Colony (ABC) to optimize the parameters of Proportional-Integral-Derivative controller (PID) of nonlinear Load Frequency Controller (LFC) for a power system. A two area non reheat thermal system is equipped with PID controller. ABC is employed to search for optimal controller parameters to minimize the time domain objective function. The performance of the proposed technique has been evaluated with the performance of the conventional Ziegler Nichols (ZN) , Genetic Algorithm (GA) and Bacterial Foraging Optimization Algorithm (BFOA) in order to demonstrate the superior efficiency of the proposed ABC in tuning PID controller. By comparison with the conventional technique, GA and BFOA, the effectiveness of the proposed ABC is validated over different operating conditions, and system parameters variations.